Toxocara Seroprevalence in Patients with Idiopathic Parkinson's Disease: Chance Association or Coincidence? - Celik, Tuncay; Kaplan, Yuksel; Atas, Eser; Oztuna, Derya; Berilgen, Said (Hindawi Ltd, 2013)
Most cases of idiopathic Parkinson disease (IPD) are believed to be due to a combination of genetic and environmental factors. The purpose of this study is to investigate the relationship between toxocariasis and Parkinson disease (PD). Patients were selected from people who were admitted to the Movement Disorders Branch, Neurology Department of Elazig University Faculty of Medicine Elazig, Turkey. We studied specific IgG antibodies against Toxocara canis (T. canis) in 50 patients with idiopathic Parkinson and 50 healthy volunteers. We investigated the clinical history of three patients infected with T. canis. We also studied specific IgG antibodies against Toxoplasma gondii in these groups. Antibodies anti-Toxocara canis were found in 3 idiopathic PD (6%) (P = 0.121) and antibody titer was not found in control. A patient had history of the presence of dog in current dog ownership. We did not detect any statistically significant association between T. canis and IPD. But, we believe that further comprehensive studies are required for understanding whether there is a causal relation between toxocariasis and PD. We didn't find possible association between Toxoplasma gondii and IPD (P = 0.617).
Keywords: Infection